VEGF-A165b protects against proteinuria in a mouse model with progressive depletion of all endogenous VEGF-A splice isoforms from the kidney - Stevens, Megan; Neal, Christopher R.; Salmon, Andrew H.J.; Bates, David O.; Harper, Steve J.; Oltean, Sebastian (Wiley, 2017)
Chronic kidney disease (CKD) is strongly associated with a decrease in the expression of VEGF-A. However, little is known about the contribution of VEGF-A splice isoforms to kidney physiology and pathology. Previous studies suggest that the splice isoform VEGF-A165b (resulting from alternative usage of a 3’ splice site in the terminal exon) is protective for kidney function. We show here, in a quad-transgenic model, that over-expression of VEGF-A165b alone is sufficient to rescue the increase in proteinuria as well as glomerular water permeability in the context of progressive depletion of all VEGF-A isoforms from the podocytes. Ultrastructural studies show that the glomerular basement membrane is thickened, podocyte slit width is increased and sub-podocyte space coverage is reduced when VEGF-A is depleted, all of which are rescued in VEGF-A165b over-expressors. VEGF-A165b restores the expression of PECAM-1 in glomerular endothelial cells and glomerular capillary circumference. Mechanistically, it increases VEGFR2 expression both in vivo and in vitro and down-regulates genes involved in migration and proliferation of endothelial cells, otherwise up-regulated by the canonical isoform VEGF-A165. Our study indicates that manipulation of VEGF-A splice isoforms could be a novel therapeutic avenue in chronic glomerular disease.